Do your worst eaudiobook - Danan, Rosie (Books on Tape, 2023)
USA TODAY BESTSELLER! Sparks fly when an occult expert and a disgraced archeologist become enemies-with-benefits in this steamy romance from "go-to author" Rosie Danan ( The New York Times Book Review ). Riley Rhodes finally has the chance to turn her family’s knack for the supernatural into a legitimate business when she’s hired to break the curse on an infamous Scottish castle. Used to working alone in her alienating occupation, she's pleasantly surprised to meet a handsome stranger upon arrival—until he tries to get her fired . Fresh off a professional scandal, Clark Edgeware can’t allow a self-proclaimed “curse breaker” to threaten his last chance for redemption. After he fails to get Riley kicked off his survey site, he vows to avoid her. Unfortunately for him, she vows to get even. Riley expects the curse to do her dirty work by driving Clark away, but instead, they keep finding themselves in close proximity. Too close. Turns out, the only thing they do better than fight is fool around. If they’re not careful, by the end of all this, more than the castle will end up in ruins.